STUDY OF THE STRESS-DEFORMED STATE OF SOILS OF LOADED ENGINEERING OBJECTS - STARODUB, Yuriy; HAVRYS, Andrii; KOZIONOVA, Olesia (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article presents examples of the use of the method of modelling the influence of the ecological and geophysical state of the soil on bridgetype objects using the finite element method. A review of publications on modelling the stress-strain state of complex bridge structures under manmade environmental influences was conducted. Examples of studying the state of loaded soils at the base of bridges built in populated areas are considered. As an example, modeling of the stress-strain state of soils under two complex bridge structures was carried out. Changes in stress-strain of such soils are shown when the loads on bridges increase and when the type of bridge structures changes. The effectiveness of using the finite element method for modelling the processes of studying and changing stresses and deformations in rocks under complex structures and identifying typical manifestations of changes in the stress-strain state, which are important for a quick assessment of the soil condition, has been confirmed.